Nutrient intake and diet quality in individuals with hyperuricemia: a matched population study - Kim, Ehn-Young; Heo, Seok-Jae; Lee, Yaeji; Han, Tae-Hwa; Kwon, Yu-Jin; Lee, Ji-Won (Frontiers in Nutrition, 2026)
BackgroundDietary factors influence hyperuricemia; however, comprehensive evaluations integrating nutrient intake, dietary patterns, and overall diet quality remain limited. This study aimed to address this gap by assessing nutrient intake using the Korean Dietary Reference Intakes (KDRIs) and diet quality using the Korean Healthy Eating Index (KHEI).MethodsIn this cross-sectional study using Korea National Health and Nutrition Examination Survey (KNHANES) data, 24,026 Korean adults were eligible prior to matching, stratified by sex, and then classified according to hyperuricemia status within each sex. After 1:1 propensity score matching based on age and body mass index, 10,268 participants were included in the final analysis. Dietary intake levels were assessed using a 24-h dietary recall, and nutrient intake and dietary quality were evaluated using the KDRIs and KHEI, respectively.ResultsThe KDRI-based analysis showed that a lower proportion of individuals with hyperuricemia met or exceeded the recommended carbohydrate intake in both sexes (men: 39.1% vs. 34.0%, p < 0.001; women: 54.0% vs. 50.1%, p < 0.001), whereas a higher proportion of women with hyperuricemia had protein intake exceeding the recommended intake levels (10.6% vs. 8.1%, p = 0.003). In the hyperuricemia group, the proportion of participants meeting the KDRIs for fiber and minerals, such as magnesium and zinc, was significantly lower in both sexes. Among men, a lower proportion met the KDRI criteria for calcium, iron, potassium, folate, and vitamins B1, B2, and C intake. The mean KHEI score was significantly lower in the hyperuricemia group than in the control group, in both sexes. Among men, the proportion of individuals with component scores ≥7 for whole grains, total fruit, fresh fruit, total vegetables, and breakfast was significantly lower in the hyperuricemia group (all p < 0.01). Among women, the hyperuricemia group consumed a lower proportion of total vegetables (p = 0.003).ConclusionThis study highlights the importance of a comprehensive dietary approach in managing hyperuricemia. These findings support the implementation of individualized strategies focused on balanced macronutrient intake, quality and sources of macronutrients, increased consumption of fiber-rich plant-based foods, adequate micronutrient intake, and healthy eating practices.